Development of Smart Board Spinner Media as a Stimulation of Numeracy Skills for 5 to 6 Year Old Children - Sari, Dewi Novita; Iriyanto, Tomas; Maningtyas, Rosyi Damayani Twinsari (Proceedings Series of Educational Studies, 2024)
Children have difficulty mastering the concepts of addition and subtraction as well as number recognition if they have poor numeracy skills and are not stimulated with learning aids. This is the reason for conducting research on the development of learning media. This research aims to present the findings of the development of the learning product "Smart Board Spinner" which offers numeracy teaching to children aged between five and six years. This research applies the ADDIE model. There are five stages in the model, namely analysis, design, development, implementation, and evaluation. The validity test results of media experts and material experts respectively obtained results of 88.8% and 93.42%. Small group trial validators got a score of 92.5% and large group trial validators got a score of 96.25%. All scores obtained show high validity. The research results show that the numeracy learning media "Smart Board Spinner". Keywords: Numeracy Skills; Children Aged 5-6 Years; Smart Board Spinner